Association between bruxism severity and serum concentrations of 25‐hydroxyvitamin D levels - Bushra A. W. Allaf; Mahmoud Abdul‐Hak (Wiley, 2022)
Abstract Objectives The aim of this study was to investigate the possible relationship between bruxism and blood levels of 25‐hydroxyvitamin D. Material and Methods One hundred male and female patients from Damascus joined the study. Their ages were in the range of 18-40 years. Two groups were considered in this study, the first group included patients who were already suffering from bruxism (76 patients) and the second group consisted of patients who were not suffering from any bruxism (24 patients). The analysis of the blood samples for 25‐hydroxyvitamin D levels of the two groups was carried out. Results The recorded results showed that there is a relationship between the levels of bruxism and 25‐hydroxyvitamin D concentration in the blood (p < .05), enhancing that the bruxism activity has been shown the associated deficiency in 25‐hydroxyvitamin D levels, which can be divided into five different categories. Conclusions Within the limitations of this study in spite of the number of patients (one hundred), according to the reported study, it appears that there is a significant relationship between bruxism and the level of 25‐hydroxyvitamin D in the blood.